2021
DOI: 10.1002/prep.202100014
|View full text |Cite
|
Sign up to set email alerts
|

Energy Release and Fragmentation of Brittle Aluminum Reactive Material Cases

Abstract: Cylindrical reactive material cases produced by the consolidation of an aluminum powder were tested via explosive launch in a closed chamber. One configuration measured the quasistatic overpressure generated by the case and explosive, and two further tests focused on soft‐catch of fragments before and after striking the chamber walls. On a volumetric basis, the reactive material cases produced two to three times the combustion energy of an aluminum 6061 alloy case or a bare nitromethane explosive that was test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The reactive materials with Zr or Al as reaction elements release energy through exothermic reaction under highspeed impact and explosion loads [1][2][3][4][5][6][7][8][9][10]. The reaction conditions and energy release characteristics of the reactive materials have been extensively studied [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reactive materials with Zr or Al as reaction elements release energy through exothermic reaction under highspeed impact and explosion loads [1][2][3][4][5][6][7][8][9][10]. The reaction conditions and energy release characteristics of the reactive materials have been extensively studied [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…F. Zhang et al [6] believed that microscopic hot spots were generated in the reactive material under explosion load, which promoted the material to break into fine fragments, made the reaction occur within sub-millisecond time, and enhanced the explosion shock wave. J. C. Kline et al [7] found that the use of MRMC can greatly increase the total combustion energy, and thicker casing will lead to insufficient material energy release. The report of N. Du et al [8] also confirmed this phenomenon and found that the thinning of MRMC under explosion is conducive to the increase of far-field air shock wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For high velocity impact conditions, strain rates between 10 3 s À 1 and 10 4 s À 1 can be expected and 10 4 s À 1 is typical for explosive events. Fragments produced from the dynamic failure of an RM system under these conditions are fragile, and typically collected using soft catch systems with low density catch mediums [2][3][4][5][6][7][8]. The use of a low density catch medium permits the fragments to be caught while mitigating additional fracture of the fragments [4].…”
Section: Introductionmentioning
confidence: 99%
“…Early soft catch systems utilized shaving cream as the catch medium [2], while current systems utilize artificial snow [3,4,[6][7][8]. The use of artificial snow simplifies the fragment extraction process, as the snow is simply melted, and water filtered to recover the fragments.…”
Section: Introductionmentioning
confidence: 99%